Health insurance coverage, healthcare use, and financial protection amongst people with disabilities in Indonesia: analysis of the 2021 National Socioeconomic SurveyResearch in context - Luthfi Azizatunnisa’; Ari Probandari; Hannah Kuper; Lena Morgon Banks (The Lancet Regional Health - Southeast Asia, 2025)
Summary: Background: Jaminan Kesehatan Nasional (JKN), Indonesia’s mandatory national health insurance scheme and the world’s largest single-payer system, has not been rigorously evaluated for its reach and effectiveness amongst people with disabilities, who often have greater healthcare needs. This study evaluates JKN coverage and its association with healthcare use and financial protection for people with disabilities in Indonesia. Methods: This cross-sectional study analysed the Indonesia National Socioeconomic Survey (Susenas) March 2021 dataset (n = 1,277,497). Disability was measured using the Washington Group Short Set (WG-SS). We used multivariate logistic regression to examine associations between disability and health insurance coverage, and between insurance coverage and healthcare utilization, out-of-pocket payments (OOP), and catastrophic health expenditure (CHE). Findings: Around 30% of people with disabilities were uninsured, and 35% were not enrolled in JKN, with coverage lower in the lowest socioeconomic groups, living in rural areas, or self-employment. Among JKN-enrolees, they were more likely to be in the subsidised group (vs. contributory) compared to those without disabilities. Overall, people with disabilities utilised healthcare services more frequently and incurred higher OOP and CHE than those without disabilities. These disparities were not mitigated by insurance coverage. Indeed, people with disabilities, even with JKN coverage, were more likely to experience high OOP and CHE, with those in the contributory group facing a higher likelihood of CHE than the subsidised group. Interpretation: There are large gaps in health insurance coverage for people with disabilities in Indonesia. Additionally, there is an urgent need to enhance the financial protection of people with disabilities, ensuring equitable and comprehensive care. Funding: This study is part of the first author’s PhD project, funded by the Indonesia Endowment Fund for Education (LPDP).